A Child’s Right to Family Life after a Care Order Is Issued: An Analysis of the Child Welfare Tribunals’ Weighting and Interpretation - Gerdts-Andresen, Tina (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2025)
This article summarizes a thesis examining how the child’s right to family life is safeguarded following a care order. The thesis consists of four studies: three analyzing the Child Welfare Tribunal’s decisions and one reviewing existing research on how children’s views are weighted in legal proceedings. The study explores how Norwegian practice aligns with human rights obligations, focusing on how the tribunal justifies restrictions on child-parent contact. Additionally, the study investigates when and how a child’s perspective is considered in decision-making processes. The findings suggest that contact regulations are often framed through a needs-based approach emphasizing placement stability rather than individualized assessments of child-parent relationships. Furthermore, while formally acknowledged, children’s perspectives appear to be selectively weighted in tribunal decisions. The discussion highlights the importance of increasing transparency in integrating competing perspectives into decision-making, strengthening professional discretion, and ensuring that child welfare practices align more closely with legal and human rights standards.